ON THE ISSUE OF THE POSSIBLE APPLICATION OF THE MEDIATION INSTITUTION IN TAX DISPUTES - O. A. Abakumova (Russian Journal of Economics and Law)
Objective: to justify the necessity to use mediation in tax disputes.Methods: the research is based on the dialectic method of cognition of mediation institution as a socio-legal phenomenon in development. The methodology of the research is general scientific methods (induction and deduction, hypothesis, generalization, abstraction, formalization,analogy, historical approach, system approach, system analysis, modeling, logical-linguistic method, etc.).Results: the benefits of mediation in tax disputes for both parties (the state and the taxpayer) were determined; it is concluded that the use of mediation in tax disputes settlement is an effective means to prevent the increase of the number of court cases and, as a consequence, contributes to the quality of justice. For greater efficiency of settling cases arising from tax legal relations, specific recommendations are proposed for the introduction of mediation; the necessity is grounded to prepare its due normative-legal regulation.Scientific novelty: the article considers the features of mediation institution functioning in the Russian Federation, and new trends in the development of this institution.Practical significance: the main provisions and conclusions of the article can be used in research and teaching in addressing issues of mediation.